The elements of style - Strunk, William (The Macmillan Company, 1959)
It aims to lighten the task of instructor and student by concentrating attention (in Chapters II and III) on a few essentials, the rules of usage and principles of composition most commonly violated. In accordance with this plan it lays down three rules for the use of the comma, instead of a score or more, and one for the use of the semicolon, in the belief that these four rules provide for all the internal punctuation that is required by nineteen sentences out of twenty. Similarly, it gives in Chapter III only those principles of the paragraph and the sentence which are of the widest application.